Análise da resiliência, bem-estar subjetivo e rendimento acadêmico de estudantes universitários da Amazônia. - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The dynamics of academia requires a high effort of college students to adapt to their demands and overcome their challenges successfully. Requiring the investigation of phenomena resilience and subjective well - being of these students. Resilience is a terminology borrowed from the hard sciences, and relates to the ability of certain materials to withstand external pressures. The subjective well - being refers to the assessment of quality of life for the individual, allowing them to think about how they feel and experience their lives. This research aimed to examine the effects of resilience on the subjective well -being and academic performance of college . The specific objectives were to identify the style of resilience of university students; investigate possible connections between styles of resilience and academic achievement and to examine possible relationships between styles of resilience and subjective well - being of the students. The theoretical framework chosen to build this work was: resilience, subjective well -being and academic performance. The survey was field with quantitative character. The instruments were administered the Brief Resilient Behavior Scale (Ribeiro; MORAL 2010 - adapted by Mascarenhas , 2011), the PANAS scale (Positive and Negative Affect Schelude) (DIENER et al, 1999, Adapted by Mascarenhas , 2008) and the Scale SWLS ( Satisfaction with Life Scale) (DIENER et al., 1985, Adapted by Mascarenhas, 2008). The sample consists of 342 students from the city of Manaus and the municipality of Humaita. Data were statistically analyzed with SPSS support. As for the results it is prudent to affirm that compared college with strong traits of resilience with with faint traces, there are disagreements on what matters to consider coping strategies. The data show that college with faint traces of resilience , feature more significantly focused on emotion coping strategy, whereas the group of students with strong traits of resilience, use problem-focused coping. Even with the data analysis it was observed that there is close relationship between the phenomena of resilience and subjective well -being, credible state that individuals with strong traits of resilience have higher scores on SWLS and PANAS scales - positive, compared with opposite group. The study failed to demonstrate the relationship between academic performance and resilience, once both strong and weak individuals with traces of resilience showed no differences. It appears then, the need for continued research to expand the supply of information associated with the topic.
Keywords: Resiliência; Rendimento Acadêmico; Academic performance; CIÊNCIAS HUMANAS: PSICOLOGIA